2021
DOI: 10.1155/2021/9960950
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Dacryodes edulis (Burseraceae) Leaves Inhibited Tumor Growth in Female Wistar Rats with 7,12-Dimethylbenz[a]anthracene-Induced Breast Cancer

Abstract: Breast cancer is the most common estrogen-dependent cancer in the world. Hormone therapy for this cancer can be neoadjuvant and/or adjuvant. Herbal remedies with antiproliferative properties are believed to be potential anticancer agents. The aqueous extract of Dacryodes edulis (Burseraceae) leaves (AE), a medicinal plant used against cancer in Cameroon, was found to display antiproliferative effects in ovariectomized rats. Compounds isolated from this plant exhibited anticancer activity in vitro. To determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…Oestrogens can lead to an increase in ROS, potentially causing oxidative damage. 37 In line with the findings of Mvondo et al 37 this study also observed an increase in mammary gland estradiol levels in female rats after exposure to DMBA. The presence of breast tumours leads to an elevation in estradiol levels, which can be attributed to the invasion of cancer cells and the growth of lobules.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Oestrogens can lead to an increase in ROS, potentially causing oxidative damage. 37 In line with the findings of Mvondo et al 37 this study also observed an increase in mammary gland estradiol levels in female rats after exposure to DMBA. The presence of breast tumours leads to an elevation in estradiol levels, which can be attributed to the invasion of cancer cells and the growth of lobules.…”
Section: Resultssupporting
confidence: 90%
“…Cell development is dependent on the presence of estrogens. 37 cancer prognosis. This marker is highly indicative of patient disease progression, regression, or stability.…”
Section: Resultsmentioning
confidence: 99%
“…Dacryodes edulis (Safou) is known for its dietary properties via its edible fruit; its curative and suppressive properties on a mouse model infected with Plasmodium berghei were demonstrated by maximum inhibition of Plasmodium at 57% and chemosuppression of the parasite at 71% [ 66 ]. In addition, this plant has antioxidant [ 67 ], anticancer [ 68 ], antidiabetic [ 69 ] properties that make it a good research model for its multiple effects. The limitation of this review is that it does not allow to conclude on the effect of these molecules on artemisinin-resistant strains which for several years has been considered as a first-line drug instead of chloroquine.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports indicating that estrogen receptors are linked to approximately 80% of breast cancers [ 87 ]. Mvondo et al, showed that the aqueous extract of D. edulis leaves reduced the tumor volume in female rats with breast cancer induced by 7,12-dimethylbenz[α]anthracene (DMBA; 50 mg/kg BW) [ 88 ]. In vitro, the cytotoxic potential of D. rostrata peels on breast cancer cell lines was determined using the MTT method.…”
Section: Bioactivity Studiesmentioning
confidence: 99%